Graded motor imagery in orthopedic and neurological rehabilitation: A systematic review of clinical studies: Graded motor imagery in rehabilitation - Candiri, Büşra; Talu, Burcu; Karabıcak, Gul Oznur (Journal of Surgery and Medicine, 2023)
Background/Aim: Graded motor imagery is an increasingly popular motion representation technique. However, treatment protocols for graded motor imagery vary depending on various diseases. This study aims to summarize the cases in which graded motor imagery therapy is used, study protocols, and outcome measures in studies. Methods: The literature search was done with Web of Science, Pubmed, Scopus, and PEDro databases. The last search was carried out on September 13, 2022. A series-specific bias risk assessment tool was used with randomized, non-randomized, and case reports. All clinical studies that performed graded motor imagery, available in full text, describing their methods and findings, were included. The gender of the participants was not significant. The intervention was graded motor imagery. Outcome measures were mainly pain severity, other pain-related measures (e.g., pressure pain threshold, pain catastrophe), range of motion, strength, reaction time, kinesiophobia, neurophysiological measures, depression, function, or quality of life measures. Results: Complex regional pain syndrome, distal radius fracture, phantom limb pain, stroke, cancer, pathological pain (phantom pain after amputation, pain after brachial plexus avulsion), elbow stiffness, frozen shoulder, chronic shoulder pain, and osteoarthritis conditions were included. The intervention duration in the studies varies from 2 to 8 weeks. A common outcome measure could not be determined among studies. The pain was assessed in 15 studies, although different rating scales were used. Graded motor imagery resulted in a reduction in pain in 14 of the 15 studies. Conclusions: Due to the heterogeneity of the studies, a general conclusion regarding the effect of the disease-specific intervention was not possible. Based on pain outcome, graded motor imagery effectively decreased pain severity in various painful conditions.